2005
DOI: 10.4103/0255-0857.16587
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and incidence of rubella in and around Delhi (1988-2002)

Abstract: National Institute of Communicable Diseases (NICD) has been engaged in rubella testing for serodiagnosis of the infection and screening for immunity status. The compiled and evaluated data of the work done on rubella testing for the past fifteen years has been presented here to show the trend and changing scenario of the disease in Delhi. Blood samples were from 7424 patients referred to NICD, Delhi for serodiagnosis of congenital Rubella syndrome (CRS) in malformed babies, in utero rubella infection in women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Rubella IgM positivity in asymptomatic pregnant women was 3.16 %. This observation was similar to studies by other investigators [10][11][12], wherein IgM positivity for rubella was 3-9 %. Rubella positivity in women with BOH was 7.72 %.…”
Section: Discussionsupporting
confidence: 93%
“…Rubella IgM positivity in asymptomatic pregnant women was 3.16 %. This observation was similar to studies by other investigators [10][11][12], wherein IgM positivity for rubella was 3-9 %. Rubella positivity in women with BOH was 7.72 %.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have been conducted in the past to know the extent of problem concerning TORCH infections in women of reproductive age, however, the sample size always remained questionable [29]. Therefore, in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Possibly, these subjects could have had a subclinical infection which went unnoticed. Studies conducted in various regions in India showed an IgM seropositivity of 6.5%, 4.9%, 9.69%, 11.3% and 4.3% respectively 7,13,14,15,16 .…”
Section: Congenital Abnormalities Following Maternalmentioning
confidence: 98%